(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objectives: To find out the proportion and maternal outcome of placenta accreta. Materials and Methods: Total 10579 deliveries were served during January 2013 to 31st December 2013 in the Department of Obstetrics and Gynecology of Addin Women Medical College Hospital, Dhaka. All patients who needed postpartum or cesarean hysterectomy for postpartum hemorrhage and diagnosed as placenta accreta after postpartum hysterectomy were included for the study. Among them who were antentally diagnosed as placenta previa with having other risk factors of placenta accreta, were evaluated by Doppler Sonography. All these cases such as diagnosed, suspected or only had multiple risk factors of placenta accreta were managed by a team approach and proper counseling of the patients guardian about need of massive transfusion, hysterectomy, Intensive Care Unit (ICU) admission . Results: Among the total 10579 deliveries 22 cases were diagnosed as placenta accreta after postpartum hysterectomy. On histopathology 8 of these cases were placenta percreta, 7 cases were placenta increta and 7 cases were placenta accreta vera. Almost ninety one (90.90%) patient had placenta previa and 90.90% patient had past H/O one or two cesarean section. Placenta percreta cases were more common in patients with H/O two previous C/S or one C /S and dilatation & curettage (D&C). In all preoperatively diagnosed cases, Right lower paramedian incision was given and hysterectomy was done leaving the placenta in situ. Conclusion: Placenta accreta is associated with previous two or more cesarean deliveries, or multigravidae with past H/O repeated D&C or M/R or combined. History of of these operations are diagnosed as having anterior or central placenta previa. Bangladesh J Obstet Gynaecol, 2013; Vol. 28(2) : 71-75